On the uncommon genera Pseudiastata Coquillett and Hyalistata Wheeler (Diptera: Drosophilidae: Steganinae): new species and additional records from the Neotropical Region - Costa, Sávio Cunha; Pirani, Gabriela; Oliveira, Sarah Siqueira (Zootaxa, 2022)
Two uncommon genera of Steganinae (Drosophilidae) are herein studied based on material from the Neotropical Region, Pseudiastata Coquillett and Hyalistata Wheeler. Additional records for Pseudiastata Coquillett are provided, including the redescription of the species Pseudiastata brasiliensis Costa Lima, originally described in 1937. An update to the morphological nomenclature is also proposed, as well as a lectotype and some paralectotype designations. Moreover, the genus Hyalistata Wheeler, for which two new species are described (Hyalistata cerradensis sp. nov. and Hyalistata emas sp. nov.) is first recorded in Brazil. We present photographs and detailed illustrations of the terminalia of all species described here.